Ketika Keheningan Berbicara: Otoritas Naratif dan Representasi Suara dalam Puisi Najwan Darwish - Hasbi Thaufik Oktodila; Syafrizal Azzali; Lianasari Lianasari; Firma Pradesta Amanah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the relationship between voice, silence, and narrative authority in three poems by Najwan Darwish: I Write the Land, The Shelling Ended, and Barely Breathing. Drawing on postcolonial theory and discourse analysis, this research employs a qualitative approach through close reading to explore how silence is represented and transformed within the poetic texts. The findings reveal that silence in these poems is not merely the absence of voice but a complex condition shaped by historical erasure, political marginalization, and psychological trauma. Furthermore, the analysis identifies a central paradox: while the poems repeatedly articulate the loss or impossibility of voice, they simultaneously function as acts of articulation. This paradox demonstrates that silence does not eliminate voice but reconfigures it into indirect, fragmented, and symbolic forms of expression. Ultimately, the study argues that poetry serves as a medium of narrative resistance, enabling marginalized voices to challenge dominant discourses and reclaim narrative authority. By articulating silence, Darwish’s poetry creates an alternative space in which suppressed experiences can be expressed, preserved, and reimagined.